Dampak Sistem Pembayaran Non Tunai terhadap JUB (M1) di Indonesia 2019-2021 - Ghalib, Ghalib; Maulida, Sri (Keizai, 2023)
The aim of this study is to evaluate the impact of non-cash payment instruments such as debit cards, e-money, and credit cards on Money Supply (M1). The research employs multiple linear regression analysis and e-views 9 data analysis tools. The results of this study indicate that debit cards have a positive and significant impact on the Money Supply (M1). In contrast, credit cards negatively and significantly impact the Money Supply (M1). On the other hand, e-money also has a positive and significant impact on the Money Supply (M1). Therefore, the conclusion drawn is that all independent variables in this study have a substantial impact on the Money Supply (M1).